Pediatric Restrictive Cardiomyopathies - Ditaranto, Raffaello; Caponetti, Angelo Giuseppe; Ferrara, Valentina; Parisi, Vanda; Minnucci, Matteo; Chiti, Chiara; Baldassarre, Riccardo; Di Nicola, Federico; Bonetti, Simone; Hasan, Tammam; Potena, Luciano; Galiè, Nazzareno; et al. (Frontiers in Pediatrics, 2022)
Restrictive cardiomyopathy (RCM) is the least frequent phenotype among pediatric heart muscle diseases, representing only 2.5-3% of all cardiomyopathies diagnosed during childhood. Pediatric restrictive cardiomyopathy has a poor prognosis, a high incidence of pulmonary hypertension, thromboembolic events and sudden death, is less amenable to medical or surgical treatment with higher mortality rates. In this scenario, heart transplantation remains the only successful therapeutic option. Despite a shared hemodynamic profile, characterized by severe diastolic dysfunction and restrictive ventricular filling, with normal ventricle ejection fraction and wall thickness, RCM recognizes a broad etiological spectrum, consisting of genetic/familial and acquired causes, each of which has a distinct pathophysiology and natural course. Hence, the aim of this review is to cover the causes, clinical presentation, diagnostic evaluation, treatment, and prognosis of pediatric RCM.